Pemanfaatan Teknologi Informasi dalam Praktik Keperawatan - Suciari, Ana; Sriyono, Sriyono (Journal of Telenursing (JOTING), 2023)
This study aims to determine the use of information technology in nursing practices. The method used is a systematic review with the preferred reporting items for systematic review and meta-analysis (prism). The search uses the Boolean phrase "information," "Technology," "Nursing Care," and "Nursing Practice". Literature studies consider original articles, sources from journals, and articles in English. They are available as complete text from international databases, e.g., Science Direct, Scopus, Sage, PubMed, and Proquest. To analyze using Joanna Briggs Institute (JBI). The results showed that information technology can help nurses in increasing collaboration and clinical, supporting decisions in facilitating the integration of clinical workflow between nurses and other medical professionals, improving the quality and efficiency of medical and maintenance services, facilitating communication management in the technology environment, increasing information documentation, Management, and monitoring, improving resource management, improving performance and satisfaction management, policy making, and facilitating the path of organizational and professional growth. CONCLUSION: IT can help nurses increase collaboration and clinical decision support in promoting the integration of clinical workflows between nurses and other medical professionals, satisfaction management, policy making, and reducing the path of organizational and professional growth. Keywords: Nursing Care, Information, Nursing Practices, Technology